2019
DOI: 10.1111/ajco.13140
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care for stage III non–small cell lung cancer in Australia

Abstract: providing medical writing support by preparing the manuscript outline, developing the first draft and collating and incorporating author comments to the final manuscript. Medical writing support was funded by AstraZeneca, Sydney, Australia in accordance with Good Publication Practice (GPP3) guidelines (http://www.ismpp.org/gpp3).Insight and stimulus for this manuscript was identified during metropolitan roundtable meetings led by AstraZeneca in Australia. Australian medical oncologists, radiation oncologists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Positron emission tomography (PET) is also used in diagnosis of NSCLC, thereby providing greater knowledge of the tumor metabolism (39). Most guidelines recommend early performance of PET to complete mediastinal staging (40), which, completed with the CT scan (PET/CT), not only enables better classification of lymph node involvement (41,42) but has also assumed greater importance with the new TNM classification. Given the frequency of brain metastasis of lung cancer, it is considered advisable to rule out brain metastases through the use of magnetic resonance imaging (MRI) in such patients, with curative intent (43).…”
Section: Clinical Characteristics Of and Therapeutic Approach To Stage IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography (PET) is also used in diagnosis of NSCLC, thereby providing greater knowledge of the tumor metabolism (39). Most guidelines recommend early performance of PET to complete mediastinal staging (40), which, completed with the CT scan (PET/CT), not only enables better classification of lymph node involvement (41,42) but has also assumed greater importance with the new TNM classification. Given the frequency of brain metastasis of lung cancer, it is considered advisable to rule out brain metastases through the use of magnetic resonance imaging (MRI) in such patients, with curative intent (43).…”
Section: Clinical Characteristics Of and Therapeutic Approach To Stage IIImentioning
confidence: 99%
“…Different reviews have shown that MDT-led management improves the quality of care, survival and quality of life of patients with stages III and IV. It is recommended that such committees include at least one pneumologist, one surgeon, one oncologist, one radiotherapist, one radiologist and one pathologist (40).…”
Section: Clinical Characteristics Of and Therapeutic Approach To Stage IIImentioning
confidence: 99%
“…Currently, there is no national lung cancer screening program in Australia due to the potentially high false-positive rates and variability of follow-up guidelines for positive results. 49 Although surgery is con-…”
Section: Interpretation Of Results and Comparison With Other Studiesmentioning
confidence: 99%
“…Currently, there is no national lung cancer screening program in Australia due to the potentially high false‐positive rates and variability of follow‐up guidelines for positive results 49 . Although surgery is considered an essential treatment in early stage lung cancer, waiting times in Australia are prioritized using an administrative rather than clinical categorization system as other elective non‐cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in reliance on limited cytotoxic chemotherapies and in particular platinum-based alkylating agents (e.g., cisplatin or carboplatin) as the backbone chemotherapy for both limited and extensive stage disease [ 9 , 10 , 12 , 13 ]. Similarly, international guidelines recommend cytotoxic chemotherapy, particularly platinum agents, as the standard of care for first-line therapy of advanced NSCLC in conjunction with targeted therapy and immunotherapy [ 2 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%